Saw mud-based functional composite filler for multiple solid wastes and preparation method thereof
Patent Information
- Application Number
- CN202611055543.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]针对现有锯泥基填料与有机基体相容性差、高填充量下力学性能下降的缺陷问题,本发明提供了一种锯泥基多元固废协同的功能性复合填料及其制备方法
[0037] (1) A ternary synergistic system of "sawdust-fly ash-slag" was constructed, realizing the high-value synergistic utilization of bulk solid waste. In the existing technology, the compounding of sawdust with fly ash and slag is mostly limited to the field of building materials, and the amount of sawdust is low (usually no more than 20 parts), which makes it difficult to reflect the value of sawdust as the main filler. This invention uses sawdust as the core component (40~70 parts), and fly ash and slag as synergistic components, with a comprehensive utilization rate of solid waste of more than 90%. On this basis, the complementary advantages of the three in terms of particle morphology, chemical composition and surface activity are fully utilized—the regular spherical particles of fly ash play the role of "micro-balls" in the system, improving the processing fluidity and dispersion uniformity of the composite filler; the high specific surface area of slag powder (≥400m²) 2The high-activity surface (/kg) provides abundant chemical bonding sites for the modifier; the irregular, fragmented particles of sawdust enhance the physical interlocking and anchoring effect between the filler and the matrix. The complementary morphology, chemical complementarity, and synergistic activity of the three components make the interfacial modification efficiency per unit mass of modifier significantly higher than that of single-component or two-component systems, achieving a synergistic effect of "1+1+1>3".
Smart Images

Figure CN122916488A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of inorganic powder material preparation technology, specifically relating to a functional composite filler prepared by synergistic use of stone processing sawdust, fly ash and slag, and its preparation method. Background Technology
[0002] Sawdust, fly ash, and slag are three types of industrial solid waste produced in huge quantities in my country. Sawdust is a major solid waste generated from stone processing, with an annual output exceeding ten million tons. Its main components are SiO2 (65%~75%) and Al2O3 (10%~18%), and it has the potential to be used as an inorganic functional filler. Fly ash has a spherical particle morphology, and slag is rich in calcium components. The chemical composition and particle morphology of the three are complementary.
[0003] Existing studies have used sawdust to replace calcium carbonate as a filler in mineral composite boards, but the sawdust was not surface-modified, and high filler content easily leads to agglomeration and decreased mechanical properties. In terms of solid waste co-utilization, existing patents disclose formulations containing various solid wastes such as sawdust, fly ash, and slag, but the amount of sawdust used is relatively low (about 8-16 parts), and it is applied in the field of cementitious materials without specifically addressing the interfacial compatibility issues of polymer fillers.
[0004] In summary, the existing technology still has the following shortcomings: (1) The surface of sawdust filler is rich in polar groups such as silanol (Si-OH) and aluminumol (Al-OH), which are hydrophilic, while the polymer matrix such as PP, PE, and PVC is non-polar or weakly polar hydrophobic material. The interfacial tension between the two is large, and when they are directly blended, the sawdust particles are difficult to be wetted by the matrix. They are prone to agglomeration due to van der Waals forces and electrostatic forces, forming stress concentration points. Under the action of external forces, crack propagation is triggered, resulting in a significant decrease in the mechanical properties of the composite material; (2) Multi-component solid waste compounding is mostly used in building materials, and there is a lack of special formulations for polymer fillers; (3) The high proportion of sawdust utilization and surface modification have not been synergistically combined. Summary of the Invention
[0005] To address the shortcomings of existing sawdust-based fillers, such as poor compatibility with organic matrices and decreased mechanical properties under high filling volumes, this invention provides a sawdust-based multi-element solid waste synergistic functional composite filler and its preparation method.
[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0007] A functional composite filler based on sawdust and synergistic effects of multiple solid wastes is characterized by being made from the following raw materials in parts by weight: 40-70 parts of stone processing sawdust, 15-30 parts of fly ash, 10-25 parts of slag powder, 0.5-3 parts of surface modifier, and 0.2-2 parts of functional additives.
[0008] The above proportion range is determined based on the following: When the amount of sawdust is less than 40 parts, the solid waste disposal rate is insufficient and the economic efficiency decreases; when it is more than 70 parts, the proportion of fine particles in the filler system is too high and the processing fluidity deteriorates. Therefore, it is limited to 40-70 parts. The spherical particles of fly ash can improve the fluidity of the system. When the amount is less than 15 parts, the fluidity improvement effect is not obvious. When it is more than 30 parts, it dilutes the main position of sawdust and the Al2O3 content is too high, affecting the matching of modifiers. Therefore, it is limited to 15-30 parts. Slag powder provides highly active surfaces and calcium components. When the amount is less than 10 parts, the activation sites are insufficient and the modification effect is limited. When it is more than 25 parts, the filler cost increases and the alkalinity of the system increases, which may affect the stability of the polymer matrix. Therefore, it is limited to 10-25 parts.
[0009] The sawdust is granite sawdust or marble sawdust, with an Al2O3 content ≥10%.
[0010] The specific surface area of the slag powder is ≥400m². 2 / kg, activity index ≥95%.
[0011] The surface modifier is selected from one or more of silane coupling agents, titanate coupling agents, stearic acid, or stearate.
[0012] The modification mechanisms of different surface modifiers are as follows: Silane coupling agents (such as KH-550 and KH-570) contain two types of functional groups—one is hydrolyzable silanoxy groups (Si-OR), which hydrolyze to form silanol groups (Si-OH), which can undergo condensation reactions with active groups such as silanol and aluminol groups on the surface of sawdust, fly ash, and slag particles to form strong covalent bonds (Si-O-Si); the other is organic functional groups (such as amino and epoxy groups), which can chemically bond or physically entangle with the polymer matrix. The coupling agent acts as a "molecular bridge" between inorganic particles and organic matrices. Titanate coupling agents are suitable for powder systems with high water content. Stearic acid / stearate mainly forms a hydrophobic organic coating layer on the particle surface through physical adsorption and chemical bonding, and has a lower cost. This invention allows for flexible selection of single or composite modifier schemes based on the surface characteristics of the three types of solid waste and the different target application matrices.
[0013] The functional additives are selected from one or more of antioxidants, light stabilizers, flame retardants, and antistatic agents.
[0014] The selection criteria for functional additives are as follows: antioxidants (such as 1010 and 1076) can inhibit the thermo-oxidative aging of the organic modified layer in the filler during processing and use; light stabilizers can improve the weather resistance of the filler in outdoor applications; flame retardants can impart flame-retardant properties to the composite material; antistatic agents can reduce static electricity accumulation on the filler surface, improve dust dispersion and uniformity during processing. When the amount of functional additive is less than 0.2 parts, the functionality is insufficient; when it is more than 2 parts, it may migrate to the surface of the composite material, affecting the appearance and mechanical properties of the product. Therefore, the dosage is limited to 0.2 to 2 parts.
[0015] The method for preparing the functional composite filler is characterized by comprising the following steps:
[0016] (1) Raw material pretreatment: The raw saw mud produced by stone processing is dehydrated by pressure filtration, sun-drying or low-temperature drying, and the moisture content is controlled to be ≤15%. It is then ground to a particle size D90≤25μm (about 600 mesh) to obtain ultrafine saw mud powder; fly ash and slag powder are dried to a moisture content ≤2%.
[0017] The selection of the ultrafine particle size range of sawdust powder is comparable to the fineness of commonly used fillers in polymer composites (such as light calcium carbonate, talc, etc.), which ensures the uniform dispersion of the filler in the matrix; at the same time, the specific surface area of sawdust powder within this particle size range is moderate (approximately 300~600m²). 2 The particle size (D90 / kg) provides sufficient surface modification active sites without excessively fine particles leading to an excessively large specific surface area, a sharp increase in modifier dosage, and a rise in processing costs. If the particle size is too coarse (D90>45μm), the filler is prone to forming large stress concentration points in the matrix, resulting in a decrease in the mechanical properties of the composite material; if the particle size is too fine (D90<10μm), the grinding energy consumption and modifier dosage both increase significantly, resulting in poor economic efficiency.
[0018] Optionally, a magnetic separation unit can be installed during the sawdust grinding process to remove ferromagnetic impurities from the sawdust and improve the whiteness of the ultrafine powder.
[0019] (2) Co-mixing of multiple solid wastes: Weigh each raw material according to the ratio of 40-70 parts sawdust, 15-30 parts fly ash and 10-25 parts slag powder, and put them into a mixer for pre-mixing to obtain mixed powder.
[0020] (3) Surface modification and activation: Add 0.5 to 3 parts of surface modifier to the mixed powder and stir and activate it at a temperature of 80℃ to 120℃ so that the surface modifier can fully coat the surface of the mixed powder particles.
[0021] The selection criteria for surface modifiers are as follows: both fly ash and slag are rich in aluminosilicate materials, and their surfaces are also rich in silanol and aluminolol active sites. The hydrolysis products of silane coupling agents can undergo condensation reactions with these active sites to form covalent bonds; slag powder has a large specific surface area (≥400m²).2 The modifier has high activity (per kg) and a higher surface hydroxyl density than ordinary powders, providing more chemical bonding sites and thus increasing the utilization rate of the modifier. Therefore, mixing the three solid wastes and modifying them uniformly allows for simultaneous coating of the modifier on the surfaces of the three particles, which is more efficient and less costly than modifying them separately and then mixing them.
[0022] To improve modification efficiency and dispersibility, a dispersant of 0.1% to 0.5% of the mass of the mixed powder can be added during the modification process. The dispersant can be selected from one or more of polyethylene glycol, sodium hexametaphosphate, or sodium tripolyphosphate.
[0023] The selection criteria and synergistic effects of the dispersants are as follows: Polyethylene glycol is a nonionic dispersant, suitable for aqueous and weakly polar systems; sodium hexametaphosphate is an inorganic anionic dispersant, preventing particle agglomeration through electrostatic repulsion and steric hindrance; sodium tripolyphosphate has both dispersing and viscosity-reducing effects. All three dispersants can reduce van der Waals forces between powder particles during the modification process, improve the uniformity of the modifier's spread on the particle surface, reduce the amount of modifier used, and shorten the activation time. When the dispersant dosage is below 0.1%, the dispersion effect is not significant; when it is above 0.5%, competitive adsorption may occur on the particle surface, affecting the chemical bonding effect of the modifier. Therefore, the dosage is limited to 0.1%~0.5%.
[0024] (4) Addition of functional additives and preparation of finished products: Add 0.2 to 2 parts of functional additives to the modified mixed powder, continue mixing for 5 to 10 minutes, cool and then sieve (through a 200 to 400 mesh sieve) to obtain the finished functional composite filler.
[0025] Preferred technical solution: The average particle size D50 of the functional composite filler is 5~15μm, and the specific surface area is 300~600m². 2 / kg.
[0026] The common technical features of this invention and the prior art are that they both involve the mixed use of sawdust with solid wastes such as fly ash and slag.
[0027] The technical features that distinguish this invention from the prior art
[0028] With sawdust as the core (40-70 parts), fly ash and slag as synergistic components, a ternary system of "sawdust + fly ash + slag" is formed, with a solid waste comprehensive utilization rate of ≥90%.
[0029] Sawdust, fly ash, and slag, three solid wastes, exhibit complementary gradations and synergistic chemical reactions in terms of particle morphology, chemical composition, and surface activity.
[0030] (a) Complementary morphology: Sawdust is an irregular shredded particle, while fly ash is a regular spherical particle. The spherical particles act as "micro-balls" in the composite filler, which can improve the dispersion, flowability and processing performance of the filler in the matrix; the high specific surface area and sharp edges of slag powder can enhance the mechanical anchoring effect between the filler and the matrix.
[0031] (b) Chemical complementarity: Sawdust is rich in SiO2 (65%~75%) and Al2O3 (10%~18%), fly ash is rich in SiO2 and Al2O3, and slag is rich in CaO and SiO2. The difference in chemical composition among the three makes the types of active sites on the surface of the mixed powder more abundant (silanol, aluminumol, calciumol, etc.), which is conducive to the multi-point chemical bonding of modifiers such as silane coupling agents;
[0032] (c) Synergistic Activity: The highly active surface of slag powder (specific surface area ≥ 400 m²) 2 / kg) can serve as an "active anchor point," preferentially adsorbing modifier molecules and forming chemical bonds during the modification process; the spherical surface of fly ash provides a uniform substrate for modifier spreading; the irregular surface of sawdust provides physical interlocking sites.
[0033] The synergistic effect of the three components makes the interfacial modification efficiency of the modifier per unit mass significantly higher than that of single-component modification.
[0034] Surface modification treatment can change the surface of solid waste powders such as sawdust from hydrophilic to hydrophobic, thereby improving their compatibility with organic polymer matrices.
[0035] Formulas are designed specifically for the functional filler needs of polymer composite materials (PP, PVC, coatings, etc.).
[0036] Compared with the prior art, the present invention has the following advantages:
[0037] (1) A ternary synergistic system of "sawdust-fly ash-slag" was constructed, realizing the high-value synergistic utilization of bulk solid waste. In the existing technology, the compounding of sawdust with fly ash and slag is mostly limited to the field of building materials, and the amount of sawdust is low (usually no more than 20 parts), which makes it difficult to reflect the value of sawdust as the main filler. This invention uses sawdust as the core component (40~70 parts), and fly ash and slag as synergistic components, with a comprehensive utilization rate of solid waste of more than 90%. On this basis, the complementary advantages of the three in terms of particle morphology, chemical composition and surface activity are fully utilized—the regular spherical particles of fly ash play the role of "micro-balls" in the system, improving the processing fluidity and dispersion uniformity of the composite filler; the high specific surface area of slag powder (≥400m²) 2The high-activity surface ( / kg) provides abundant chemical bonding sites for the modifier; the irregular, fragmented particles of sawdust enhance the physical interlocking and anchoring effect between the filler and the matrix. The complementary morphology, chemical complementarity, and synergistic activity of the three components make the interfacial modification efficiency per unit mass of modifier significantly higher than that of single-component or two-component systems, achieving a synergistic effect of "1+1+1>3".
[0038] (2) The "unified surface modification" technical solution fundamentally solves the interfacial compatibility problem between sawdust-based fillers and polymer matrices. Existing technologies for surface modification of solid waste fillers often target single components or simply mix the separately modified products, resulting in complex processes and low modifier utilization. This invention performs overall surface coating modification on three types of mixed solid waste powders. It utilizes the silanoxy groups in modifier molecules such as silane coupling agents to form covalent bonds with the abundant silanol, aluminum hydroxyl, and calcium hydroxyl groups on the surface of the three particles. Simultaneously, the organic functional groups of the modifier molecules chemically bond or physically entangle with the polymer matrix, creating a "molecular bridge" between the inorganic particles and the organic matrix. This "unified modification" scheme simultaneously transforms the surfaces of the three solid waste particles from hydrophilic to hydrophobic, significantly improving compatibility with non-polar / weakly polar polymer matrices such as PP, PE, and PVC. This process is simpler and more efficient than the separate modification and mixing process, and the modification effect is superior.
[0039] (3) It overcomes the technical defect of "difficulty in achieving both rigidity and toughness" of a single filler and achieves simultaneous improvement of the mechanical properties of composite materials. Due to poor dispersibility and weak interfacial bonding, single sawdust filler often leads to a significant decrease in the impact toughness and elongation at break of composite materials at high filler contents, i.e. "increased rigidity and decreased toughness". This invention, through the combination of ternary synergy and surface modification, enables the composite filler to play an excellent dual role of reinforcement and toughening in the PP matrix.
[0040] (4) The system constructs a complete process chain from solid waste raw materials to functional filler products, which has excellent industrial promotion value and market adaptability. This invention addresses the characteristics of sawdust raw materials such as high moisture content and uneven particle size, designing a complete process route of "pressure filtration / dehydration / low-temperature drying → ultrafine grinding (D90≤25μm) → magnetic separation for iron removal (optional) → multi-component formulation → unified surface modification → functional additive compounding → sieving of finished product". The process flow is clear, the equipment is highly versatile, and it can be industrialized and promoted in stone processing parks or solid waste comprehensive utilization bases. Furthermore, by adjusting the ratio of sawdust to fly ash and slag, as well as the type and amount of surface modifiers / functional additives, a series of functional filler products that meet the needs of different polymer systems such as PP, PE, PVC, rubber, and coatings can be flexibly prepared, possessing broad market application prospects and flexible product customization capabilities. Attached Figure Description
[0041] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0042] Figure 1 This is a schematic diagram of the process flow of this application. Detailed Implementation
[0043] To gain a deeper understanding of this invention, we will provide a comprehensive and detailed description. However, this invention has various implementations and is not limited to the specific examples listed herein. These examples are presented to enhance a full understanding of the disclosure of this invention.
[0044] Example 1 (medium sawdust content, used for PP modification)
[0045] (1) Raw materials: Granite sawdust (after pressure filtration, dehydration, and drying) produced by a stone processing plant in Shandong Province was used. It was grayish-white powder with a measured moisture content of 15.3%. The main dry basis components were: SiO2 70.2%, Al2O3 13.5%, Fe2O3 1.3%, CaO 1.8%, MgO 0.9%, K2O 4.2%, Na2O 3.1%, and loss on ignition 4.2%. The fly ash was Class II fly ash with a loss on ignition ≤6%; the slag powder was S95 grade with a specific surface area of 450 m². 2 / kg.
[0046] (2) Pretreatment: The sawdust is ground in a ball mill to a particle size D90≤25μm, and the output specific surface area is about 380m². 2 / kg; dry fly ash and slag powder separately to a moisture content ≤2%.
[0047] (3) Ingredients and surface modification: 50 kg of sawdust, 25 kg of fly ash, and 20 kg of slag powder were added to a mixer and mixed. 1.0 kg of silane coupling agent KH-550 and 0.5 kg of stearic acid were added as composite surface modifiers and activated by high-speed stirring at 95°C. Then, 0.2 kg of sodium hexametaphosphate dispersant and 0.4 kg of antioxidant 1010 were added and mixed, and the mixture was passed through a 300-mesh sieve to obtain the finished product.
[0048] (4) Application effect: The obtained composite filler was added to polypropylene (PP) at a filling amount of 35%, and the mixture was granulated by twin-screw extrusion and injection molded to prepare samples. The test results showed that the tensile strength retention rate of the composite material was more than 95% of that of pure PP, and the flexural modulus was increased by about 40%.
[0049] Example 2 (High sawdust content, used for PVC modification)
[0050] (1) Raw materials: Granite sawdust (after pressure filtration, dehydration, and drying) produced by a stone processing plant in Shandong Province was used. It was grayish-white powder with a measured moisture content of 15.3%. The main dry basis components were: SiO2 70.2%, Al2O3 13.5%, Fe2O3 1.3%, CaO 1.8%, MgO 0.9%, K2O 4.2%, Na2O 3.1%, and loss on ignition 4.2%. The fly ash was Class II fly ash with a loss on ignition ≤6%; the slag powder was S95 grade with a specific surface area of 450 m². 2 / kg.
[0051] (2) Pretreatment: The sawdust is ground in a ball mill to a particle size D90≤25μm, and the output specific surface area is about 380m². 2 / kg; dry fly ash and slag powder separately to a moisture content ≤2%.
[0052] (3) Batching and surface modification: 65 kg of sawdust, 18 kg of fly ash, and 12 kg of slag powder were added to a mixer and mixed. 1.2 kg of silane coupling agent KH-560 was added and activated by high-speed stirring at 100°C. 0.3 kg of antioxidant 1076 was then added and mixed, and the mixture was passed through a 300-mesh sieve to obtain the finished product.
[0053] (4) Application effect: The composite filler was added to PVC at a filling amount of 20%, along with calcium-zinc stabilizer and lubricant. The samples were then subjected to open milling and hot pressing. The results showed that the composite material had good processing fluidity, the surface of the product was smooth, and the mechanical properties met the general requirements for the use of plastic products.
[0054] Comparative Example
[0055] To demonstrate that the technical solution of this application produces a technical effect that differs from the prior art, the following comparative examples are set up:
[0056] Comparative Example 1 (sawdust filler only)
[0057] Using only the ultrafine sawdust powder from Example 1 (without adding fly ash and slag powder), surface modification was performed separately at 95 kg of sawdust (1.0 kg of KH-550 + 0.5 kg of stearic acid, activated at 95°C), and then added to PP at a 35% filler content, and its mechanical properties were tested.
[0058] Comparative Example 2 (sawdust + fly ash, no slag)
[0059] The materials were prepared by mixing 70 kg of sawdust and 25 kg of fly ash (excluding slag powder), and added to PP under the same modification conditions and filling amount as in Example 1. The mechanical properties were then tested.
[0060] Comparative Example 3 (sawdust + slag, no fly ash)
[0061] The materials were prepared by mixing 70 kg of sawdust and 25 kg of slag powder (excluding fly ash), and added to PP under the same modification conditions and filling amount as in Example 1. The mechanical properties were then tested.
[0062] Comparative Example 4 (Unmodified ternary composite filler)
[0063] The materials were prepared according to the proportions in Example 1 (50kg sawdust + 25kg fly ash + 20kg slag powder), but without surface modification treatment, and directly added to PP at a filling amount of 35% to test its mechanical properties.
[0064] Comparative Example 5 (modified separately and then mixed)
[0065] Sawdust, fly ash, and slag powder were individually modified with KH-550 at a mass ratio of 100:1.0 (activated at 95℃). Then, the three modified products were mixed according to the ratio in Example 1 and added to PP at a filling amount of 35%, and their mechanical properties were tested.
[0066] Table 1
[0067]
[0068] It can be seen from the above table:
[0069] (1) Comparison of Example 1 and Comparative Example 1 (sawdust only): The tensile strength (34.2 MPa) of Example 1 is higher than that of Comparative Example 1 (30.5 MPa), the flexural modulus (1890 MPa) is much higher than that of Comparative Example 1 (1620 MPa), and the impact strength (4.2 kJ / m) is also higher. 2 The value is much higher than that of Comparative Example 1 (3.1 kJ / m³). 2 The results demonstrate that the introduction of fly ash and slag produced a significant synergistic enhancement effect—the spherical fly ash particles improved the dispersibility of the filler, while the highly active surface of the slag enhanced the bonding efficiency of the modifier and the interfacial bonding strength.
[0070] (2) Comparison of Example 1 and Comparative Example 2 (sawdust + fly ash, no slag): The tensile strength (34.2 MPa) of Example 1 is higher than that of Comparative Example 2 (31.8 MPa), and the impact strength (4.2 kJ / m) is higher. 2 The value is much higher than that of Comparative Example 2 (3.5 kJ / m³). 2 The results demonstrate that the introduction of slag powder significantly contributes to improving the impact toughness of the composite material, and its highly active surface provides more chemical bonding sites for the modifier.
[0071] (3) Comparison of Example 1 and Comparative Example 3 (sawdust + slag, no fly ash): The flexural modulus (1890MPa) of Example 1 is higher than that of Comparative Example 3 (1750MPa), and the melt flow index (5.8g / 10min) is higher than that of Comparative Example 3 (5.2g / 10min), indicating that the spherical particles of fly ash improve the processing fluidity of the system.
[0072] (4) Comparison of Example 1 and Comparative Example 4 (unmodified): The mechanical properties of Comparative Example 4 are significantly lower than those of Example 1, with the tensile strength decreasing from 34.2 MPa in Example 1 to 26.8 MPa, and the impact strength decreasing from 4.2 kJ / m 2 Decreased to 2.5 kJ / m 2 This demonstrates that surface modification is a necessary prerequisite for achieving a good interfacial bond between solid waste fillers and polymer matrices.
[0073] (5) Comparison of Example 1 and Comparative Example 5 (modified separately and then mixed): The mechanical properties of the two are relatively similar, but the tensile strength of Example 1 (34.2 MPa) is slightly better than that of Comparative Example 5 (33.5 MPa), and the impact strength is 4.2 kJ / m. 2 It is also superior to the 3.9 kJ / m of Comparative Example 5. 2 The results show that the process of uniformly modifying the three solid wastes after mixing not only simplifies the production process and reduces costs, but also achieves a slightly better modification effect than mixing them after separate modification because the three particles are dispersed in the mixed state and the modifier is more evenly distributed on the surface of the mixed powder.
[0074] (6) Comparison of Example 1 and pure PP: The flexural modulus of Example 1 (1890MPa) is about 40% higher than that of pure PP (1350MPa), the tensile strength retention rate is about 105% (32.5MPa→34.2MPa), and the impact strength retention rate is about 110% (3.8kJ / m). 2 →4.2kJ / m 2 This achieved a "strength and toughness enhancement" effect, proving that the ternary synergistic modified composite filler plays an excellent dual role in reinforcing and toughening PP.
[0075] The comparative results above demonstrate that the ternary synergistic system of "sawdust + fly ash + slag" and the unified surface modification technology of this invention produce significant synergistic effects. Sawdust provides the main silica-alumina component and filler skeleton; the spherical particles of fly ash improve processing fluidity and dispersion uniformity; and the highly active surface-reinforcing modifier of slag powder enhances bonding efficiency and interfacial bonding strength. The three components are complementary in morphology, chemically complementary, and synergistic in activity, resulting in composite materials with significantly better overall mechanical properties than single-component or two-component solutions. The unified modification process is simpler and more efficient than the process of modifying separately and then mixing, leading to superior modification results. All three components are indispensable; the absence or simplification of any step will lead to a significant decrease in the performance of the final product, proving that the various technical features of this invention have a close synergistic relationship, rather than a simple additive one.
[0076] Contents not described in detail in this specification are prior art known to those skilled in the art. Although illustrative specific embodiments of the invention have been described above to facilitate understanding by those skilled in the art, it should be understood that the invention is not limited to the scope of the specific embodiments. Various modifications are readily apparent to those skilled in the art as long as they fall within the spirit and scope of the invention as defined and determined by the appended claims, and all inventions utilizing the concept of this invention are protected.
Claims
1. A functional composite filler based on sawdust sludge and synergistic effects of multiple solid wastes, characterized in that, Made from the following parts by weight of raw materials: 40-70 parts of stone processing sawdust; 15-30 parts fly ash; 10-25 parts of slag powder; 0.5-3 parts of surface modifier; Functional additives: 0.2-2 parts; The particle morphology, chemical composition, and surface activity of the sawdust, fly ash, and slag powder form a complementary gradation and chemical synergy. The surface modifier is used to coat the mixed powder of sawdust, fly ash and slag powder, so that the surface of the three solid waste particles changes from hydrophilic to hydrophobic at the same time.
2. The functional composite filler according to claim 1, characterized in that, The sawdust is granite sawdust or marble sawdust, with an Al2O3 content ≥10%; the slag powder has a specific surface area ≥400m². 2 / kg, activity index ≥95%.
3. The functional composite filler according to claim 1, characterized in that, The surface modifier is selected from one or more of silane coupling agents, titanate coupling agents, stearic acid, or stearate.
4. The functional composite filler according to claim 1, characterized in that, The functional additives are selected from one or more of antioxidants, light stabilizers, flame retardants, and antistatic agents.
5. The functional composite filler according to any one of claims 1 to 4, characterized in that, The functional composite filler has an average particle size D50 of 5~15μm and a specific surface area of 300~600m². 2 / kg.
6. A method for preparing a sawdust-based multi-element solid waste synergistic functional composite filler as described in any one of claims 1 to 4, characterized in that, Includes the following steps: (1) Raw material pretreatment: The raw sawdust generated from stone processing is dehydrated and dried to control the moisture content ≤15%, and then ground to a particle size D90≤25μm to obtain ultrafine sawdust powder; fly ash and slag powder are dried to a moisture content ≤2% respectively; (2) Co-processing of multiple solid wastes: Weigh each raw material according to the ratio of 40-70 parts sawdust, 15-30 parts fly ash and 10-25 parts slag powder, and mix them to obtain a mixed powder. (3) Surface modification and activation: Add 0.5 to 3 parts of surface modifier to the mixed powder and stir and activate it at a temperature of 80℃ to 120℃ so that the surface modifier is coated on the surface of the mixed powder particles; (4) Addition of functional additives: Add 0.2 to 2 parts of functional additives to the modified mixed powder, continue mixing, and after cooling, the functional composite filler product is obtained.
7. The preparation method according to claim 6, characterized in that, The particle size D90 of the ultrafine sawdust powder mentioned in step (1) is ≤25μm.
8. The preparation method according to claim 6, characterized in that, In step (3), a dispersant of 0.1% to 0.5% of the mass of the mixed powder is added during the modification process. The dispersant is selected from one or more of polyethylene glycol, sodium hexametaphosphate, or sodium tripolyphosphate.
9. The preparation method according to claim 6, characterized in that, In step (1), a magnetic separation iron removal unit is set up during the sawdust grinding process to remove ferromagnetic impurities from the sawdust.
10. The use of the functional composite filler according to any one of claims 1 to 4 in polypropylene, polyethylene, polyvinyl chloride or coatings.